Gated communities and land administration challenges in Ghana: reappraising the reasons why people move into gated communities. Issue 3 (16th March 2021) - Ehwi, Richmond Juvenile; Morrison, Nicky; Tyler, Peter
Abstract: Gated communities are proliferating in most developing countries. Scholars, however, continue to rely on mainstream demand-based arguments mostly framed in developed countries to explain this phenomenon, without giving sufficient attention to context-specific factors. Presenting the case of the Greater Accra Metropolitan Area in Ghana and using household surveys and key informant interviews, this article emphasizes Ghana's land administration challenges and demonstrates how these challenges influence people's reasons to move into gated communities. Using principal component analysis, our results show that land administration challenges significantly influenced the decisions of households living in inner-city gated communities relative to their counterparts in peri-urban areas. However, in peri-urban areas, both mainstream demand-based arguments and land administration challenges were equally influential. Household and expert interviews illuminate our results. Although, empirically, this paper focuses on Ghana, the importance of the land factor and its spatio-temporal dimension has considerable resonance elsewhere, as scholars across the globe grapple with understanding why gated communities continue apace.